Strategic Competence Developed by Students during English Debate Activity - Hutama, Dilis Priyuana (Jurnal Penelitian Pendidikan, 2019)
This study was a case study aimed to find out strategic competence developed by students during English debate activity.The participants of the study were 6 students from the English Club of SMP Negeri 18 Semarang. In obtaining the data, the researcher conducted some steps. The first, the researcher conducted observation and recorded it. The second, the researcher transcribed the debate of the students. The third, the researcher identified and classified the strategic competence of the students by Tarone (1980)’s theory. Then the researcher counted and gave percentage the result data. Based on the result of the data, the researcher interpreted it. It is shown that the strategic competence developed is 154. The highest frequency is Language Switch, that is 24.03%. The second highest frequency is Message Abandonment with 14.29%. The third is Literal Translation with 13.63%. The fourth is Mime with 12.99%. The fifth is Topic Avoidance with 11.69%. The sixth is Appeal for Assistance with 8.44%. The seventh is Word Coinage with 7.14%. The eighth is Approximation with 4.54%. The lowest frequency is Circumlocution with 3.25%. The results showed that all of students developed strategic competence by Tarone (1980). The strategic competence developed by student debaters is affected by some reasons covering to maintain their position as debaters, to maintain the flow of the debate, and to conceal their lack of English vocabularies.